Flouting of maxim by Indian-American and American characters in the Never Have I Ever Series - Nordin, Nurul Aina Amelia; Anuar, Nadia (Universiti Teknologi MARA, 2024)
Successful communication requires adherence to conversational implicatures. Failure to observe maxims can lead to misunderstandings and conflicts, particularly in intercultural settings. Hence, to address these issues, it is critical to improve public understanding of Grice's conversational implicatures theory. Therefore, the purpose of this study is to compare the use of Grice's conversational implicatures theory by two main characters from distinct cultural back-grounds who are Indian-American and American in the series: Never Have I Ever. This research used a qualitative methodology and utilises Grice’s conversational implicatures to analyse the implicatures by the Indian-American character and the American character in the series: Never Have I Ever. The data was analysed using content analysis. The study found that the Indian-American character flouted a total of 18 maxims, encompassing all four types: (1) maxim of quality, (2) quantity, (3) manner, and (4) relation. In contrast, the American character flouted 6 maxims, in-volving three types: (1) maxim of quality, (2) manner, and (3) relation. Furthermore, the research identified cultural influences, including low and high context cultures, power distance, and individualism versus collectivism, as contrib-uting factors to the usage of flouting maxims. This research aims to improve intercultural interactions and foster inclu-sivity by assisting intercultural students in understanding communication differences and raising public awareness of cross-cultural communication dynamics. Future research opportunities were also discussed, such as exploring a wider range of literary compositions, incorporating diverse cultural perspectives, and utilising alternative methodologies.